Muscle Physiopathology in Parathyroid Hormone Disorders - Romagnoli, Cecilia; Brandi, Maria Luisa (Frontiers in Medicine, 2021)
Parathyroid hormone disorders are a group of diseases in which secretion of parathormone (PTH) is impaired. The disorders that result are characterized by signs and symptoms associated with the persistent presence of high blood calcium levels (hypercalcemia) related to hyperparathyroidism (PHPT), or reduced blood calcium levels (hypocalcemia) associated with hypoparathyroidism (HypoPT). In addition to the resulting alteration in bone microarchitecture and mass for both pathologies, patients also report problems with skeletal muscle due to a decrease in muscular strength, muscular dysfunction, and myopathies, which can be responsible for an increased risk of instability and fracture. Although the effect of PTH on bone is well established, and numerous studies suggest that PTH has an effect on skeletal muscle, knowledge about cellular e molecular mechanisms of action on skeletal muscle is very limited. Skeletal muscle is a tissue well known for its structural and mechanical actions and is endowed with an extraordinary ability to adapt to physiological changes. Research in skeletal muscle has increased over the last decade, its importance as an endocrine tissue also emerging, becoming itself a target of numerous substances and hormones. Parathyroid hormone disorders represent a starting point to understand whether PTH may have an effect on skeletal muscle. This review analyzes the basic research data reported to date on PTH and skeletal muscle, highlighting the importance of increasing our knowledge in this field of research.